Perlawanan Masyarakat Samin Terhadap Kolonialisme Belanda di Bojonegoro Tahun 1890-1917 - Lintang Oktafia; Nasution N (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examines the resistance of the Samin community to Dutch colonialism in Bojonegoro between 1890 and 1917. Previous studies have primarily positioned Blora and Rembang as the main centers of the Samin Movement, while Bojonegoro has generally been treated only as an area of its expansion. As a result, the relationship between local conditions in Bojonegoro, the control of teak forests, taxation, village obligations, and forms of Samin resistance has not been discussed comprehensively. This study aims to explain the background of the movement and analyze its forms of resistance within the social, economic, and political context of Bojonegoro. It employs the historical method, consisting of heuristics, source criticism, interpretation, and historiography. The sources include colonial archives, government regulations, forestry reports, official investigations of the Samin Movement, contemporary newspapers, and oral testimonies. James C. Scott’s theory of everyday resistance is used as an analytical framework. The findings show that colonial control over land, forests, labor, taxation, and village administration restricted the community’s living space. Samin teachings then became a moral foundation for rejecting these policies. Resistance took the form of refusing to pay taxes, rejecting compulsory labor, opposing state control over forests and village granaries, and disobeying administrative regulations. The colonial government responded through surveillance, arrests, exile, and official investigations.